English Writing Problems of Non-English Department Students - Barnaba, Hengki Yudha; Rahmawan, Andi Dian (Journal of English Teaching and Learning Issues, 2019)
This research sheds a light on students’ problems on writing English paragraphs, the special attention would be given to the way students generating proper vocabulary and lexeme and the word orders.  The researchers attempt to reveal the relationship between students’ learning preferences during the process of English learning in senior high school and the error being produced while producing the academic texts or paragraphs.This is a survey research by employing 50 students as the research subjects from department of Elementary School Teacher Training and Mathematic Education of University of PGRI Yogyakarta. They are, both female and male, from various background and amount of exposure to English. Students were asked to produce four paragraphs, narrating the process of English learning during the high school. The errors are classified into errors in diction and error in word orders. The researchers make relation between the error and the learning styles being implemented during the school process. The results would be descriptively explainedBased on the research results, it is revealed that Kinesthetic was the most-used method by the students who have the highest level of English comprehension. The reason is that the students are scaffolding, doing something to support the learning process. So, the learning goals are easily comprehended. It is strongly suggested that the teachers do carefully consideration to find the best approaches to teach materials by recognizing all students learning preferences in a classroom.